Rev-Erb co-regulates muscle regeneration via tethered interaction with the NF-Y cistrome - Ryan D. Welch; Chun Guo; Monideepa Sengupta; Katherine J. Carpenter; Natalie A. Stephens; Stacy A. Arnett; Marvin J. Meyers; Lauren M. Sparks; Steven R. Smith; Jinsong Zhang; Thomas P. Burris; Colin A. Flaveny (Elsevier, 2017)
Objective: The loss of skeletal muscle mass and strength are a central feature of traumatic injury and degenerative myopathies. Unfortunately, pharmacological interventions typically fail to stem the long-term decline in quality of life. Reduced Rev-Erb-mediated gene suppression in cultured C2C12 myoblasts has been shown to stimulate myoblast differentiation. Yet the mechanisms that allow Rev-Erb to pleiotropically inhibit muscle differentiation are not well understood. In this study, we sought to elucidate the role of Rev-Erb in the regulation of muscle differentiation and regeneration in vivo. Methods: Using Rev-Erbα/β shRNAs, pharmacological ligands, and Rev-Erbα null and heterozygous mice, we probed the mechanism of Rev-Erbα/β regulation of muscle differentiation and muscle regeneration. Results: ChIP seq analysis of Rev-Erb in differentiating myoblasts showed that Rev-Erbα did not transcriptionally regulate muscle differentiation through cognate Rev-Erb/ROR-response elements but through possible interaction with the cell fate regulator NF-Y at CCAAT-motifs. Muscle differentiation is stimulated by Rev-Erb release from CCAAT-motifs at promoter and enhancer elements of a number of myogenesis proteins. Partial loss of Rev-Erb expression in mice heterozygous for Rev-Erbα accelerated muscle repair in vivo whereas Rev-Erb knockout mice showed deficiencies in regenerative repair compared to wild type mice. These phenotypic differences between heterozygous and knockout mice were not apparently dependent on MRF induction in response to injury. Similarly, pharmacological disruption of Rev-Erb suppressive activity in injured muscle accelerated regenerative repair in response to acute injury. Conclusions: Disrupting Rev-Erb activity in injured muscle accelerates regenerative muscle repair/differentiation through transcriptional de-repression of myogenic programs. Rev-Erb, therefore, may be a potent therapeutic target for a myriad of muscular disorders.